Analisis Pengaruh Investasi, Pajak Daerah, Tenaga Kerja Terhadap Produk Domestik Regional Bruto Kabupaten/Kota Provinsi Jawa Timur Tahun (2015-2019) - Septian Gilang Kusuma; M.Sri Wahyudi (Jurnal Ilmu Ekonomi, 2021)
The purpose of this study is to determine the effect of the variable Investment (PMDN), Regional Tax and Labor (Working Force) on the Gross Regional Domestic Product (PDRB-ADHK) in the Regency/City of East Java Province. The analytical tool used is panel data regression. From the results obtained, the value of the determinant coefficient R^2 for the model used is the Fixed Effect of 0.929335. Where it shows the dependent variable is 92.93%. So that the results of the study can be concluded that simultaneously Investment, Regional Tax and Labor have a positive and significant effect on Gross Regional Domestic Product (PDRB) with F statistic 48.65 greater than F-table. While the results of the partial test show that investment, local taxes and labor have a significant positive effect on Gross Regional Domestic Product (PDRB).